2017
DOI: 10.1097/pcc.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Low Cardiac Output Syndrome Score Is Associated With Morbidity in Infants After Congenital Heart Surgery*

Abstract: Higher peak Low Cardiac Output Syndrome Score and cumulative Low Cardiac Output Syndrome Score were associated with increased morbidity and resource utilization among infants following surgery for congenital heart defects and might be a useful tools in future cardiac intensive care research. Independent validation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The secondary outcome was LCOS and for this study LCOS for POD 1(post-op day1 arrival from OR to CICU until midnight), POD 2 and POD 3 was studied and was classified into five categories as mild : single vasoactive agent or arterial lactate < 2; moderate : two vasoactive agents or arterial lactate between 2 to 5; severe : three or more vasoactive agents or arterial lactate > 5; mechanical support : requirement of extracorporeal membrane oxygenation (ECMO) or ventricular assist devices (VAD); and finally, death . This endpoint was chosen because elevated lactate levels and more number of vasoactive agents with higher dosage have been associated with worse clinical outcomes 1, 15, 16 .…”
Section: Methodsmentioning
confidence: 99%
“…The secondary outcome was LCOS and for this study LCOS for POD 1(post-op day1 arrival from OR to CICU until midnight), POD 2 and POD 3 was studied and was classified into five categories as mild : single vasoactive agent or arterial lactate < 2; moderate : two vasoactive agents or arterial lactate between 2 to 5; severe : three or more vasoactive agents or arterial lactate > 5; mechanical support : requirement of extracorporeal membrane oxygenation (ECMO) or ventricular assist devices (VAD); and finally, death . This endpoint was chosen because elevated lactate levels and more number of vasoactive agents with higher dosage have been associated with worse clinical outcomes 1, 15, 16 .…”
Section: Methodsmentioning
confidence: 99%
“…A point is given for each indicator that is present. In the prospective evaluation of LCOSS carried out by Ulate et al (11), measurements of LCOSS were recorded at arrival on CICU, and at 8,12, and 24 hours postoperatively and used to calculate a peak and cumulative LCOSS, and in a single centre study this was found to be strongly linked to a composite measure of post-operative morbidity.…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
“…The LCOSS score for the equivalent 12 hour period was calculated for each of the study patients based on the clinical and laboratory criteria set out by Ulate et al (11). One difference in the application of the LCOSS score in our study was that data were retrospective, hence the timing of measurements could not be controlled, hence we refer to this as a modified LCOSS (mLCOSS).…”
Section: Methodsmentioning
confidence: 99%
“…Several scoring systems have been created that are designed to evaluate patients for the condition and predict poor outcomes in the postoperative period. 16,17 Ulate et al 17 developed an LCOS score that used specific criteria to identify LCOS; they found the score to be useful as a predictor of morbidity and resource use in their patient population. Such scoring systems may serve as useful bedside nursing tools facilitating awareness of the presence of LCOS and appropriate communication with the medical team.…”
Section: Discussionmentioning
confidence: 99%